A clue for obstructive sleep apnea hidden in tomographic images of idiopathic pulmonary fibrosis patients - Şahin Duyar, Sezgi; Ertürk, Hakan; Fırat, Selma; Çelik, Deniz (The European Research Journal, 2021)
Objectives: The most common opinion about apnea/hypopnea formation in restrictive pulmonary diseases is based on decreased lung volumes causing upper airway collapse. This study targets to reveal some evidence for this pathophysiological pathway in patients with idiopathic pulmonary fibrosis (IPF) and obstructive sleep apnea (OSA). Methods: The clinical, demographical, and polysomnographic characteristics of 19 patients with OSA and IPF who underwent all-night polysomnography (PSG) were retrospectively evaluated for investigating the correlations between lung volumes calculated on the images of high-resolution computed tomography (HRCT) and polysomnographic findings. Supine HRCT images performed at the time of diagnosis of IPF were used for the calculation of total lung volume and low attenuation areas of the lung (LAA). The results were compared with the results of the PSG and pulmonary function tests (PFT). Results: The study group comprised 19 patients (3 female, 16 male) with a median apnea-hypopnea index (AHI) of 23.5/h. AHI in this IPF cohort was not correlated with body-mass index, neck circumference, age, or PFT. However, overall AHI and non-rapid eye movement (non-REM) AHI had a trend of positive correlation with LAA. We also showed a positive correlation between the LAA and forced vital capacity (FVC) (r=0.682 and, p = 0.003). Conclusions: The severity of OSAS in IPF patients is well correlated with LAA. This result supports the gravitational and the volumetric effect of the lung in apnea-hypopnea formation.